Mathematic Learning Using Discovery Learning Model to Improve Students' Critical Thinking Skills - Nasrulloh, Muhammad Farid; Satiti, Wisnu Siwi; Ningrum, Ayu Septian (SCHOOLAR: Social and Literature Study in Education, 2025)
This study was conducted with the aim of knowing the process and effect of discovery learning to improve critical thinking skills of Vocational School NU Al-Hidayah students as many as 10 students for test questions and 21 students for the application of learning using the discovery learning model. In this study, the teaching module was prepared using the discovery learning model which consisted of 6 learning syntaxes and was conducted for 2 meetings. The research method used is a pre-experimental design with the type of one-group pretes-posttes design and uses a quantitative research approach. The test instrument was in the form of pretest and posttest description questions to measure students' critical thinking skills. The data analysis technique used is hypothesis testing. However, before testing the hypothesis, the data obtained was first tested for normality. Based on the results of the data normality test with Shapiro-Wilk, the pretest results have a significance value of 0.113 and the posttest results have a significance value of 0.253. The normality test is normal. Based on the paired sample t-test calculation, it shows that the t value is 0.000 with a significance of 0.000. The significance value shows 0.000 < the error rate of 0.05, so it can be concluded that Ha is accepted. Acceptance of Ha means that there is a positive influence on the critical thinking skills of students in class X APHP Vocational School NU Al- Hidayah after applying the paired sample t-test.